The impact of consumption value on consumer behaviour: A case study of halal-certified food supplies - Muhamed, Ariff Azly; Ab Rahman, Mohd Nizam; Mohd Hamzah, Firdaus; Che Mohd Zain, Che Rosmawati; Zailani, Suhaiza (Emerald, 2019)
Purpose: The purpose of this paper is to investigate the influence of halal concern as well as emotional and epistemic values on consumer behaviour in the choice and purchase of halal-certified food supplies. Design/methodology/approach: This study used a quantitative methodology of convenience sampling to collect survey data from 1,550 Muslim respondents in Malaysia. It also employed multiple regressions by covariance-based structural equation modelling in the data analysis as well as in the validation of the proposed model. Findings: The empirical results showed that the importance of halal certification had the highest impact on consumer choice behaviour, particularly in the purchase of halal-certified food supplies. Also, epistemic and emotional values were both statistically significant in terms of their influence on the consumer decision-making process. Research limitations/implications: The results emphasize the importance of enhancing the hedonic (halal concern and emotional value) aspect as a way for the halal food industries to obtain an added value advantage for their products and services. Originality/value: This paper is the first to employ an empirical approach to consider the halal sentiment as a determinant of consumer purchasing behaviour in the context of halal-certified food supplies. © 2019, Emerald Publishing Limited.